2021
DOI: 10.1002/star.202000193
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Effect of Citric Acid on Microstructure, Rheology, and Structural Recovery of Thermoplastic Potato Starch

Abstract: The main objective of the present work is to explore the role of citric acid (CA) on microstructural changes and their impact on the melt rheological behavior, mechanical performance, and shape recovery of thermoplastic starch (TPS). The results of frequency sweep test show a pronounced nonterminal storage modulus (G’) at lower frequencies (high melt elasticity) for TPS, which is found to be greatly reduced in favor of improving the processability through the addition of CA. This could be explained in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…The hydrolysed amylopectin chain behaves like the linear amylose chain, promoting stable single helix crystalline formation during drying. The same observation was also found in the study of Javidi et al 21 where they found that the TPCS chain liberated from the amylopectin has a high potential to recrystallize into a single helix helical structure during the post-processing stage. Besides that, they also concluded that adding the carboxylic acids could effectively reduce the retrogradation in the corn starch films due to the cross-linking reaction between the TPCS chains.…”
Section: Crystalline Structure Of Cr-tpcs and Cr-4b1c Studies Through...supporting
confidence: 82%
See 3 more Smart Citations
“…The hydrolysed amylopectin chain behaves like the linear amylose chain, promoting stable single helix crystalline formation during drying. The same observation was also found in the study of Javidi et al 21 where they found that the TPCS chain liberated from the amylopectin has a high potential to recrystallize into a single helix helical structure during the post-processing stage. Besides that, they also concluded that adding the carboxylic acids could effectively reduce the retrogradation in the corn starch films due to the cross-linking reaction between the TPCS chains.…”
Section: Crystalline Structure Of Cr-tpcs and Cr-4b1c Studies Through...supporting
confidence: 82%
“…Coplasticization between glycerol and carboxylic acid has higher plasticization effect than single plasticizer system (glycerol) in reducing the intermolecular interaction of the TPCS chains and promoting higher film's flexibility. Co-plasticization has higher efficiency to disrupt the intra and inter-molecular structure of TPCS and promote greater dynamic motions of the molecules 21 Generally, the CA-TPCS films showed marginally higher tensile strength and Young's modulus than the TA-TPCS films in their respective pH values. The different mechanical properties between the CA-TPCS and TA-TPCS may be attributed to the different carboxyl groups in their chemical structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crosslinking of starches with crosslinkers such as CA, [ 6‐9 ] STMP, [ 10‐13 ] and epichlorohydrin [ 14 ] have reported to introduce intra‐ and inter‐molecular bonds at selected hydroxyl (─OH) groups of two adjoining intact starch molecule. It mainly occurrs in the amorphous region of starch, and induces amylopectin–amylopectin and amylose–amylopectin crosslinking.…”
Section: Introductionmentioning
confidence: 99%